Design and wrench-feasible workspace analysis of a cable-driven hybrid joint. (9th January 2020) - Zhang, Shan; Cao, Dongxing; Min, Hong; Li, Shuai; Zhang, Xinglei
This article proposes a cable-driven hybrid joint (CDHJ), focuses on the effects of external wrench payload and structural parameters on the wrench-feasible workspace for the preliminary design of the mechanism, and further discusses the wrench exertion capability of the mechanism under a certain configuration. This CDHJ has central rigid support with a revolute pair and a central compression spring support. Due to the unilateral property of cables and the flexible compression spring, the kinematic model cannot define the workspace directly; it should be combined with the statics for possible solution, including the spring lateral buckling model based on the elliptic integral solution. Moreover, a global tension index which is to evaluate the wrench-closure property of the global workspace, combined with an index which is to assess the size of the workspace, is proposed to better compare the effects of different external wrench payloads and different structural parameters on the workspace. Simulations were performed and demonstrated the correctness and feasibility of the inverse kinematics and workspace analysis of the joint. Hence, the proposed mechanism has potential use in robotics especially in wheelchair-mounted robotic manipulator joint.